Indonesian Muslim Diaspora in Contemporary South Korea: Living as Religious Minority Group in Non-Muslim Country - Srimulyani, Eka (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
The process of migration and cross border mobility occurs for a number of reason or background such as politics, economics, education and so forth has made a number of Muslim leave their homeland to another countries. Due to this migration, a significant number of Muslims becomes a diasporic communities in other countries and sometimes lives as religious minority group in non-Muslim country. It is reported that one third of Muslims in the world live as minority in a number of countries both in the West and also in some Asian countries such as India, Japan, South Korea, etc. In general, the existing academic discourse and publication has focused more Muslim in the West, and overlooked the Muslims minority in Eastern countries which is also considered as non-Muslim land such as Japan, South Korea, and such. This article discusses the Muslim minorities in South Korea, with a specific focus on Indonesian Muslim as it made up a significant number of Muslim in South Korea recently. Their challenge, balancing their personal identity and loyal citizenship as well as integration issues will also discussed from fiqh (Islamic jurisprudence) of minorities (fiqh al-aqaliyyat) point of view.